Integrating Artificial Intelligence in Productive Waqf Management to Support the Sustainable Development Goals (SDGs) - Andi Fika Widuri (Badan Wakaf Indonesia, 2026)
This paper explores the integration of Artificial Intelligence (AI) in productive waqf management as a strategy to enhance transparency, efficiency, and social impact in alignment with the Sustainable Development Goals (SDGs). Despite waqf’s vital role in Islamic social finance, many institutions continue to rely on manual systems, resulting in inconsistent reporting, inefficient asset use, and limited impact measurement. These challenges often arise not from religious constraints, but from human capacity gaps and institutional hesitation to embrace innovation. As a result, waqf struggles to address pressing social issues such as poverty, inequality, and access to education. As waqf evolves from a traditional charitable model into a strategic development tool, digital transformation particularly through AI opens new possibilities for data-driven decision-making and real-time monitoring. This study employs a qualitative-comparative approach based on desk research to develop a conceptual framework for integrating AI into key components of waqf management: asset allocation, beneficiary targeting, impact evaluation, and financial reporting.The paper also reflects on the varying digital readiness among Indonesian regions and explores the potential for piloting AI-assisted waqf in areas with strong wakaf assets but weak management structures. Comparative insights from countries such as Malaysia and the UAE are included to contextualize best practices and feasibility. While the study does not explore AI technicalities in depth, it highlights key opportunities and non-technical challenges such as digital literacy, institutional capacity, and policy alignment. The paper concludes with recommendations for inclusive and ethical AI adoption to strengthen SDG-oriented waqf reform by 2030.